2007
DOI: 10.1089/jam.2007.0614
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heliox on the Output and Particle-Size Distribution of Salbutamol Using Jet and Vibrating Mesh Nebulizers

Abstract: There are theoretical benefits of delivering drug aerosols to patients with asthma and COPD using Heliox as a carrier gas. The objective of this study was to develop systems to allow bronchodilators nebulised by a breath enhanced jet nebuliser and a vibrating mesh nebuliser to be delivered to patients in Heliox. This was achieved by attaching a reservoir to the nebulisers to ensure inhaled Heliox was not diluted by entrained air. For the vibrating mesh nebuliser, the total output was significantly higher after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This result is consistent with the data of O'Callaghan and colleagues, (16) wherein a similar difference was reported between air and He/O 2 for the Aeroneb Pro. In the present work, when the supplied gases were humidified differences in droplet sizes between air and He/O 2 were less pronounced, suggesting that these differences were related to droplet evaporation between nebulization and measurement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the data of O'Callaghan and colleagues, (16) wherein a similar difference was reported between air and He/O 2 for the Aeroneb Pro. In the present work, when the supplied gases were humidified differences in droplet sizes between air and He/O 2 were less pronounced, suggesting that these differences were related to droplet evaporation between nebulization and measurement.…”
Section: Discussionsupporting
confidence: 93%
“…As such, the influence of He/O 2 on aerosol delivery during NIV should be evaluated for a given combination of delivery device and breathing circuit prior to employing that combination for coadministration of He/O 2 and aerosol therapy. Further, as He/O 2 is known to affect droplet size distributions delivered from jet nebulizers, (14)(15)(16)(17) and, though less so, from vibrating mesh nebulizers, (16,18) these modalities of aerosol delivery may require particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…Fink and colleagues (Fink, 2006;Fink, Heramia, Bathe, & Watson, 2003) reported nearly identical droplet sizes, as measured by laser diffraction, in oxygen and He/O 2 for the Aeroneb Pro (Aerogen Ltd., Ireland) vibrating mesh nebulizer. Working with the same nebulizer, but using a cascade impactor for aerosol sizing, O'Callaghan et al (2007) measured a small reduction in median droplet size in He/O 2 compared to air; however, an explanation of this effect was not provided.…”
mentioning
confidence: 99%
“…For jet nebulizers, atomization of a liquid medication is driven by a pressurized supply of gas accelerated through a nozzle, and brought into contact with a liquid surface. When these nebulizers are supplied with He/O 2 , the lower density of He/O 2 compared to air results in a smaller energy available for atomization at equivalent supplied volume flow rates, leading to the production of larger droplets (Corcoran, Dauber, Chigier, & Iacono, 2002;O'Callaghan et al, 2007;Piva, Menna Barreto, Zelmanovitz, Amanté a, & Cox, 2002), and to a lower aerosol output rate (Corcoran et al, 2002;Hess, Acosta, Ritz, Kacmarek, & Camargo, 1999;O'Callaghan et al, 2007). While these effects can be overcome by increasing the supplied flow rate of He/O 2 , the necessity to adjust operating conditions in order to achieve the same performance in He/O 2 as in air, and to perform adequate testing to confirm said performance, may be seen as obstacles in the clinical use of He/O 2 with medical aerosols.…”
mentioning
confidence: 99%
“…They used the percentage of particles that are smaller than 5 microns as the criteria to evaluate the medication performance of a nebulizer. They found that by changing the carrier gas into a lighter gas, the percentage increased (O'Callaghan et al, 2007). However, most of the researchers concentrated on the mechanical factors of a nebulizer as well as focused on the medication properties in the nebulizer.…”
Section: Research Gapmentioning
confidence: 99%